A scanning beam antenna fed by a 7 × 8 Butler matrix for 5G applications. Issue 5 (21st February 2022) - Wu, Ming; Zhang, Bing; Zhou, Yanping; Huang, Kama
Abstract: A 7 × 8 Butler matrix (BM) beam‐forming network operating at Ka ‐band is proposed to feed a 8 × 8 slot array. By merging the two central input ports of the BM into one port, the BM can provide output signals with equal phase, thereby generating a boresight beam. Measured results show that the proposed antenna has impedance bandwidth of 29.5–30.5 GHz, while the gain lies in the range of 14.7–21.8 dBi. Seven beams are realized, including a boresight beam, covering the range from −58° to 58°. In order to verify this concept, the feeding network and antenna are designed and manufactured. The measured results are in good agreement with simulation. It is a capable candidate for 5G mobile terminal applications.